2022
DOI: 10.3389/fcvm.2022.990063
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-based targeting of cardiac arrhythmias by phytochemicals and medicinal herbs: A comprehensive review of preclinical and clinical evidence

Abstract: Cardiac arrhythmias, characterized by an irregular heartbeat, are associated with high mortality and morbidity. Because of the narrow therapeutic window of antiarrhythmic drugs (AADs), the management of arrhythmia is still challenging. Therefore, searching for new safe, and effective therapeutic options is unavoidable. In this study, the antiarrhythmic effects of medicinal plants and their active constituents were systematically reviewed to introduce some possible candidates for mechanism-based targeting of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 111 publications
0
6
0
Order By: Relevance
“…Free curcumin has been reported to have beneficial effects against several cardiac arrhythmias [ 143 , 144 , 145 , 146 ], attributed, among other actions, to its antioxidant properties [ 147 ]. It has also been demonstrated that an encapsulated lipopolymeric hybrid nanoparticle formulation of curcumin, while enhancing the bioavailability and stability of the compound, could protect against QT prolongation by activating the hERG (human ether-a-go-go-related gene) K+ channel, in a manner superior to liposomal curcumin [ 148 ].…”
Section: Curcumin and Curcuminoidsmentioning
confidence: 99%
“…Free curcumin has been reported to have beneficial effects against several cardiac arrhythmias [ 143 , 144 , 145 , 146 ], attributed, among other actions, to its antioxidant properties [ 147 ]. It has also been demonstrated that an encapsulated lipopolymeric hybrid nanoparticle formulation of curcumin, while enhancing the bioavailability and stability of the compound, could protect against QT prolongation by activating the hERG (human ether-a-go-go-related gene) K+ channel, in a manner superior to liposomal curcumin [ 148 ].…”
Section: Curcumin and Curcuminoidsmentioning
confidence: 99%
“…So, the only area where the current can pass nodes from the atria through the ventricle is at the centre AV node. This is why we can introduce the AV node as a special electrical window or specialized electrical connection between the atria and the ventricle (Soltani et al 2022).…”
Section: Junctional or Nodal Arrhythmiamentioning
confidence: 99%
“…Efficiently removing MB from water is an important issue and has aroused extensive attention in academic field during the past few years. Variety of physicochemical techniques have been explored to eliminate organic dyes from waste liquid, such as precipitation (Sabboh et al 2006), adsorption (Petit and Bandosz 2011), ion exchange (Horcajada et al 2006), photocatalysis (Soltani et al 2022) and electrochemical (Zhang et al 2020). Among the above methods, adsorption has been an excellent unit operation to be widely applied in industrial production owing to its low cost, convenient operation and low sensitivity to toxicants.…”
Section: Introductionmentioning
confidence: 99%